УЗАГАЛЬНЕНЕ ВИЗНАЧЕННЯ ПОВНОЇ ПОТУЖНОСТІ ТА ЕНЕРГОЕФЕКТИВНИХ СТРАТЕГІЙ АКТИВНОЇ ФІЛЬТРАЦІЇ В СКОРОЧЕНОМУ КООРДИНАТНОМУ БАЗИСІ БАГАТОФАЗНОЇ СИСТЕМИ ЕЛЕКТРОЖИВЛЕННЯ - Артеменко, М.Ю.; Кутафін, Ю.В.; Чопик, В.В.; Михальський, В.М.; Шаповал, І.A.; Поліщук, С.Й. (Інститут електродинаміки НАН України, Київ, 2025)
The paper substantiates the equivalence of determining the apparent power of a multiphase power supply system with different transmission line impedances using the Fryze-Buchholz-Deppenbrock method and on a reduced coordinate basis. Two energy-efficient control strategies for shunt active filtering in the reduced coordinate basis are proposed. The first strategy provides a unit value of the power factor, and the second strategy minimizes power losses in the transmission line while maintaining symmetry and the quasi-sinusoidal shape of the consumed currents. The advantages of using a reduced coordinate basis are a reduction in the number of sensors and key active filter regulators as well as the absence of the problem to organize the artificial grounding point for phase voltage measurements. A correction factor for the apparent power and power factor formulas was determined and verified in the presence of restrictions on the symmetrical and sinusoidal shape of the consumed currents. References 22, figures 5, tables 2.